Feeding juvenile largemouth bass (Micropterus salmoides) with carboxymethyl cellulose with different viscous: Impacts on nutrient digestibility, growth, and hepatic and gut morphology - Liu, Yu; Fan, Jiongting; Zhou, Hang; Zhang, Yumeng; Huang, Huajing; Cao, Yixiong; Zhang, Wei; Deng, Junming; Tan, Beiping (Frontiers in Marine Science, 2022)
A 56-day trial investigated the impacts of dietary inclusion of different viscous cellulose on the growth, nutrient digestibility, serum biochemical indices, and hepatic and gut morphology of largemouth bass juveniles. Four practical diets (42.50% protein and 13.70% lipid) were designed containing 8% microcrystalline cellulose (MC), carboxymethyl cellulose (CMC) with 2500, 5000 and 6500 mPa•s (named MC, Lvs-CMC, Mvs-CMC, and Hvs-CMC groups), respectively. Fish with uniform size (6.0 g) were randomly assigned into 16 cages with 40 fish per cage. Results showed that the protein and lipid deposition rate, specific growth rate, protein efficiency ratio, and weight gain rate decreased significantly in the CMC groups compared to the MC group, whereas the feed intake and feed coefficient rate exhibited an opposite trend. Moreover, the intestinal Na+/K+-ATPase, alkaline phosphatase, and lipase activity significantly decreased in the Mvs-CMC and Hvs-CMC groups compared to the MC group, as well as the serum triglyceride, total cholesterol, and high/low-density lipoprotein contents. Nutrient apparent digestibility significantly decreased in the CMC groups compared to the MC group. Viserosomatic and intestinal length indices in the CMC groups and villus height in the Hvs-CMC group were significantly lower than in the MC group, whereas the gut goblet cell numbers and muscular thickness in the Mvs-CMC and Hvs-CMC groups exhibited an opposite result. Results exhibited that dietary CMC damaged hepatic and gut morphology, decreased digestive enzyme activity, nutrient apparent digestibility, and growth of largemouth bass. In summary, viscosity is the main anti-nutritional effect of dietary CMC and soluble non-starch polysaccharides.